Correlation of The Concept of Property Rights in Islamic Law and KUHPerdata - Muhammad Irkham Firdaus (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2022)
Abstract: The nature of property rights to an object in Islam is absolute belongs to Allah, human ownership is only majazi. It is different from the concept of property rights in KUHPerdata, that property rights are control over an object and take advantage of the object. However, the concept of property rights according to Islamic law and KUHPerdata has a very significant correlation. As in the causes and mechanisms of obtaining ownership rights in KUHPerdata, which must go through claims that are in line with the concept of Ihrazul Mubahat (creating permissibility) in Islam. Because the ownership of Participation/Attachment is in line with the concept of At-Tawalud min al-mamluk (with increase or birth). The concept of past time/expiration is in harmony with Al-Uqud (Testament). The concept of inheritance is in line with Al-Khalafiyat (Replacement) or the concept of inheritance. While the concept of surrender is in line with the concept of ownership in Islam, namely al-muhabat. Istila 'al-muhabat or the way of ownership through control of property. The correlation of property rights in Islamic law and KUHPerdata can also be proven by the arguments in the Qur'an and Hadith, so that it can strengthen the belief of the Muslim community to comply with the ownership rights laws listed in KUHPerdata.Abstrak: Hakekat hak milik terhadap suatu benda dalam Islam adalah mutlak milik Allah, kepemilikan manusia hanya bersifat majazi. Berbeda dengan konsep hak milik dalam KUHPerdata, bahwa hak milik adalah penguasaan terhadap suatu benda dan mengambil manfaat dari benda tersebut. Akan tetapi konsep hak milik menurut hukum Islam dan KUHPerdata memiliki kolerasi yang sangat signifikan. Sebagaimana dalam sebab dan mekanisme memperoleh hak kepemilikan pada KUHPerdata yang harus melalui pendakuan selaras dengan konsep Ihrazul Mubahat (menimbulkan kebolehan) dalam Islam. Sebab kepemilikan  Ikutan/Perlekatan selaras dengan konsep At-Tawallud min al-mamluk (dengan pertambahan atau kelahiran). Konsep lampaunya waktu/daluwarsa selaras dengan Al-Uqud (Perjanjian). Konsep pewarisan selaras dengan Al-Khalafiyat (Penggantian) atau konsep waris. Sedangkan konsep penyerahan selaras dengan konsep kepemilikan dalam Islam, yaitu al-muhabat. Istila’ al-muhabat atau cara kepemilikan melalui penguasaan terhadap harta. Kolerasi hak milik dalam hukum Islam dan KUPerdata tersebut juga dapat dibuktikan dengan dalil-dalil dalam Al-Qur’an dan Hadist, sehingga dapat meperkuat keyakinan masyarakat muslim untuk mematuhi udang-undang hak kepemilikan yang tercantum dalam KUHPerdata.